A Preliminary proteomics-based assessment of biotic indicators in Central Mexican water bodies biotic indicators by proteomics in Mexican water bodies - Catalina E. Gardella-García; Eduardo Domínguez-de-la-Cruz; Gerardo Pérez-Ramírez; Randy E. David; Juan Enrique Chacón-Hernández; Sandra Cotino-Nájera; María de Lourdes Muñoz (PLoS ONE, 2026)
Human activities such as industrialization, recreation, domestic water use, agriculture, and energy production have significantly increased pollution in water bodies, especially within urban regions. This pollution affects ecological biodiversity, exerting broad impacts on various environmental and public health factors. In response, this study utilized proteomic analysis to characterize the macro- and microbiota community compositions of natural water bodies located across diverse urban and semi-urban regions. Our strategy involved collecting samples from Mexico City as well as the Mexican states of Mexico, Morelos and Guanajuato. Samples were analyzed using liquid chromatography, coupled with High Resolution Mass Spectrometry (LC-HDMS), to detect organisms. Using this approach, we identified protein peptide sequences belonging to diverse taxa, including Plantae, Animalia, Protozoa and Bacteria, encompassing both pathogenic and non-pathogenic organisms. Some identified pathogens are known contributors to disease outbreaks in Mexico. Additionally, other detected organisms provided insights into the ecological structure and biodiversity of the regions surrounding each sampled water body. Further analyses included assessments of species richness, relative abundance, and overall biological diversity. Results provide a fundamental proteomic basis for studying biodiversity in Mexican water bodies, which may serve as a reference for future longitudinal research. Moreover, this approach offers a powerful method for detecting and modeling water contamination caused by human activity.